2021
DOI: 10.31234/osf.io/mzswb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moral dilemmas and trust in leaders during a global health crisis

Abstract: Trust in leaders is central to citizen compliance with public policies. One potential determinant of trust is how leaders resolve conflicts between utilitarian and non- utilitarian ethical principles in moral dilemmas. Past research suggests that utilitarian responses to dilemmas can both erode and enhance trust in leaders: sacrificing some people to save many others (‘instrumental harm’) reduces trust, while maximizing the welfare of everyone equally (‘impartial beneficence’) may increase trust. In a multi-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For instance, managerial and organizational practices, political processes and personal relationships between patients and healthcare providers may hinder or promote trust within health systems (Gilson, 2006). In the context of health crises, trust in health systems and authorities gains importance as a requisite for compliance with policies and measures and, therefore, for the effective management of the situation (Everett et al, 2021).…”
Section: Trust and Healthcarementioning
confidence: 99%
“…For instance, managerial and organizational practices, political processes and personal relationships between patients and healthcare providers may hinder or promote trust within health systems (Gilson, 2006). In the context of health crises, trust in health systems and authorities gains importance as a requisite for compliance with policies and measures and, therefore, for the effective management of the situation (Everett et al, 2021).…”
Section: Trust and Healthcarementioning
confidence: 99%
“…Different from previous work inferring utilitarianism from responses to sacrificial dilemmas, research guided by the two-dimensional model of utilitarian psychology infers endorsement of IH and IB from participants’ agreement with broad ethical statements about key ideas of the two dimensions (Kahane et al, 2018). Previous work using this approach has shown that the two dimensions of utilitarianism show different patterns of correlations with individual-difference measures (Kahane et al, 2018), are affected differently by priming manipulations (Capraro et al, 2019), and have distinct consequences for social perception (Everett et al, 2018, 2021). Moreover, although endorsement of pro-sacrificial harm in moral dilemmas has been found to be positively correlated with IH, moral dilemma judgments were found to be unrelated to IB (Kahane et al, 2018).…”
Section: The Current Researchmentioning
confidence: 99%